The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3892/or.2013.2529
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic effects of oxymatrine on pancreatic cancer by inhibition of the NF-κB-mediated VEGF signaling pathway

Abstract: Oxymatrine, the main alkaloid component in the traditional Chinese herbal medicine Sophora japonica (Sophora flavescens Ait), has been reported to have antitumor properties. However, the mechanisms of action in human pancreatic cancer are not well established to date. In the present study, we investigated the antiangiogenic effects of oxymatrine on human pancreatic cancer as well as the possible mechanisms involved. The results of the cell viability assay showed that treatment of PANC-1 pancreatic cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 31 publications
1
45
0
Order By: Relevance
“…In human osteosarcoma MNNG/HOS cell line, oxymatrine induces mitochondria dependent apoptosis by inhibiting the PI3K/Akt pathway (15). In an in intro and in vivo experiment, oxymatrine shows an antiangiogenic effect on pancreatic cancer through inhibition of the NF-κB-mediated VEGF signaling pathway (16).…”
Section: Diterpenoidmentioning
confidence: 99%
“…In human osteosarcoma MNNG/HOS cell line, oxymatrine induces mitochondria dependent apoptosis by inhibiting the PI3K/Akt pathway (15). In an in intro and in vivo experiment, oxymatrine shows an antiangiogenic effect on pancreatic cancer through inhibition of the NF-κB-mediated VEGF signaling pathway (16).…”
Section: Diterpenoidmentioning
confidence: 99%
“…Extensive research over the past decades have revealed various important pharmacological activities of oxymatrine under in vitro and in vivo conditions, including anti-inflammation, immunoregulatory, antihepatitis virus infection, antihepatic fibrosis, antianaphylaxis, and other immune regulation. [11][12][13][14][15] Recently, oxymatrine has been extensively studied for their cancer chemopreventive potential against various cancers, for instance, human pancreatic cancer, 16 gastric cancer, 17 breast cancer, 18 lung cancer, 19 osteosarcoma, 20 and leukemia. 21 However, the precise mechanisms underlying the anticancer activity of oxymatrine are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oxymatrine protected animals against ischemia and reperfusion-induced liver, heart, and intestinal injuries involving extracellular signal regulated kinase, c-Jun N-terminal kinase, and p38 mitogen-activated protein kinases signaling pathways [19][21]. In addition, the inhibitory effect of oxymatrine on NF-κB signaling pathway has been reported in pancreatic cancer [22] and cerebral ischemia in animals [23]. However, the effect of oxymatrine on NF-κB signaling pathway and the association with intestinal epithelial barrier dysfunction is unclear.…”
Section: Introductionmentioning
confidence: 99%